2018
DOI: 10.1002/nop2.213
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of experiences of health and social care in home mechanical ventilation

Abstract: Aim To contribute insight into health and social care integration through an exploration of the care experiences of adults with degenerative neuromuscular conditions who use a mechanical ventilator at home. Design Descriptive qualitative research. Methods Seventeen semi‐structured interviews were conducted with patients and family carers living in Scotland during 2015–2016 and thematically analysed. Results To achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…In the German study of Schaepe and Ewers, one of the respondents described the total necessity of trusting one's nurse [30], which reflects this high feeling of dependence. Similar feelings of patients concerning their caregivers were described in a Scottish study by MacLaren et al [31].…”
Section: Discussionsupporting
confidence: 77%
“…In the German study of Schaepe and Ewers, one of the respondents described the total necessity of trusting one's nurse [30], which reflects this high feeling of dependence. Similar feelings of patients concerning their caregivers were described in a Scottish study by MacLaren et al [31].…”
Section: Discussionsupporting
confidence: 77%
“…The present review gives insights into the users' mental health based on a wide range of reported mental health outcomes in a setting in which no therapeutic alternatives exist and users would die from their illness without treatment. In relation to the subcomponent positive affect, home mechanical ventilation gave people an interest in the lived life, which is confirmed by an international analysis by MacLaren et al (2019). Moreover, MacLaren et al (2019 reported that home mechanical ventilation does not by itself make it possible to live a satisfying life.…”
Section: Discussionmentioning
confidence: 67%
“…Despite a potentially negative impact on self-efficacy resulting in complacency, both patients and carers reported an increase in confidence due to the remote monitoring. It is recognised that domiciliary NIV is associated with a high carer burden 27 28. The results of this study suggest the use of remote monitoring can increase confidence of carers.…”
Section: Discussionmentioning
confidence: 71%